1999
DOI: 10.1034/j.1600-0420.1999.770407.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival of glaucoma patients

Abstract: ABSTRACT.Purpose: To investigate the survival of patients with capsular or simple glaucoma compared with that of the common population, with particular attention to the impact of sex and use of acetazolamide (Diamox). Methods: The 30 year survival of 1147 patients with capsular or simple glaucoma who were finally hospitalized at the Eye Department, Rikshospitalet, Oslo, from 1961 to 1970, are analysed, using log rank tests. The time varying impacts of sex and acetazolamide on survival are also studied using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
1
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 9 publications
4
24
1
1
Order By: Relevance
“…However, it has been postulated that an association could possibly arise as an adverse complication of OAG treatment or due to a common overlapping pathogenic pathway. 13 Acetazolamide treatment for OAG is known to be associated with an increased risk of mortality, 14 and the systemic effects of other IOP-modulating medications are well established. 13 Lee et al 7 identified a significant relationship between topical b-blocker use and cardiovascular mortality.…”
Section: Resultsmentioning
confidence: 99%
“…However, it has been postulated that an association could possibly arise as an adverse complication of OAG treatment or due to a common overlapping pathogenic pathway. 13 Acetazolamide treatment for OAG is known to be associated with an increased risk of mortality, 14 and the systemic effects of other IOP-modulating medications are well established. 13 Lee et al 7 identified a significant relationship between topical b-blocker use and cardiovascular mortality.…”
Section: Resultsmentioning
confidence: 99%
“…3,[5][6][7] One study 5 showed the lowest survival rate to be among males using acetazolamide. In our study, of the 23 pairs of patients who could be considered for visual field progression, the male/female mix in each group was identical (Table 5).…”
Section: Discussionmentioning
confidence: 99%
“…1 Even on treatment, an estimated 9% of the patients will become bilaterally blind after 20 years of treatment. 2 Some studies have considered glaucoma and its relationship to shortened survival, [3][4][5][6][7] Others have considered the effects of systemic disease on glaucomatous progression. 8,9 These studies, however, do not consider poor life expectancy as a factor in glaucomatous progression.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years the possibility of a reduced survival rate among glaucoma patients has indeed been reported by no less than three quite different studies [10,19,24]. Other recent studies do not confirm, but cannot exclude, such a possibility [5,23,39]; therefore, "no clear relationship has emerged from research on this issue" [26].…”
Section: Introductionmentioning
confidence: 96%